COMPARATIVE ASSESSMENT OF THE BIOPHYSICAL PROFILE OF FETAL IN WOMEN WITH RH - NEGATIVE BLOOD WITH AND WITHOUT IMMUNIZATION - Najmutdinova D. K; Akhtamova M. N (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this thesis, Comparative assessment of the biophysical profile of fetal in women with rh - negative blood with and without immunization is analyzed. The analysis was carried out in 23 pregnant women. Most of them were their 24 (82%), whereas age of other part pregnants was between 25 and 30 (2%).